1975
DOI: 10.2190/0yjk-tj4c-5ut0-93wm
|View full text |Cite
|
Sign up to set email alerts
|

Retirement to the Porch in Rural Appalachia

Abstract: Successful retirement in old age depends on the existence of a set of social arrangements in which a person has accumulated a considerable longtime social standing that justifies his claims for support from the community. In a small, rural Appalachian settlement, the pattern of retirement to the porch illustrates how claims by old men for social attention and care are anchored in the interests of others and are vested with significance for the entire community. While the use of the porch to facilitate the asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…There are a number of studies, however, that do suggest that friendship relations and neighborhood sociability may be stronger in rural areas, at least for the elderly. A study by Lozier and Althouse (1975) suggests that the rural elderly may be more likely than the urban to remain highly involved in social and community activities, and that the rural elderly may be more likely to receive support from local organizations. Bultena,Powers,Falkman and Frederick (1 971) found the rural elderly in Iowa to be more satisfied with the neighborliness of their communities, and Hampe and Blevins (1972) found that 97 percent of their rural respondents felt that they could rely on neighbors for help in a crisis.…”
Section: Possible Compensations Of Rural Residencementioning
confidence: 99%
“…There are a number of studies, however, that do suggest that friendship relations and neighborhood sociability may be stronger in rural areas, at least for the elderly. A study by Lozier and Althouse (1975) suggests that the rural elderly may be more likely than the urban to remain highly involved in social and community activities, and that the rural elderly may be more likely to receive support from local organizations. Bultena,Powers,Falkman and Frederick (1 971) found the rural elderly in Iowa to be more satisfied with the neighborliness of their communities, and Hampe and Blevins (1972) found that 97 percent of their rural respondents felt that they could rely on neighbors for help in a crisis.…”
Section: Possible Compensations Of Rural Residencementioning
confidence: 99%
“…The results suggest that the elderly may be primary beneficiaries of rural "natural helpers" programs which seek to strengthen existing social networks (D'Augelli & Ehrlich, 1982). These social networks may be relatively weak in the instance of the elderly who have migrated back into rural communities having lived the major portion of their lives in areas that were geographically distant (Lozier & Althouse, 1975).…”
Section: Discussionmentioning
confidence: 96%
“…Outside the home, the "surveillance zone," space within the visual field of the dwelling, assumes special significance for many rural old people (Lozier & Althouse, 1975;Rowles, 1981a;Wang, 1979). In addition to important practical and social reciprocity between old people and their neighbors, the fact that much time is spent on the porch or at the window, watching events within the visual field-the children playing and the passing cars-and being watched, means that this space assumes increasing significance as physical limitations dictate progressively more time spent at home.…”
Section: Cognitions Of Spacementioning
confidence: 99%
“…In addition to important practical and social reciprocity between old people and their neighbors, the fact that much time is spent on the porch or at the window, watching events within the visual field-the children playing and the passing cars-and being watched, means that this space assumes increasing significance as physical limitations dictate progressively more time spent at home. Lozier and Althouse provide a sensitive interpretation of the significance of this zone as an arena in which the old person is still able to exert important social control as he or she becomes increasingly vulnerable (Lozier & Althouse, 1975). Of course such benefits cannot be fully enjoyed by those rural residents who live "out in the country" beyond the visual field of neighbors or major roads.…”
Section: Cognitions Of Spacementioning
confidence: 99%